Insulin-like growth factors 1 and 2 regulate gene expression and enzymatic activity of cyp17a1 in ovarian follicles of the yellowtail, Seriola quinqueradiata - Kentaro Higuchi (Heliyon, 2020)
There is accumulating evidence that insulin-like growth factors (IGFs), primary mediators of somatic growth, play an important role in fish reproduction. Previously, we showed that IGF-1 and IGF-2 are expressed in the ovarian follicle cells of the yellowtail (Seriola quinqueradiata) during the vitellogenic phase, suggesting that IGFs may be involved in ovarian steroidogenesis. In this study, we examined the effects of IGF-1 and IGF-2 on gene expression and activity of steroidogenic enzymes in yellowtail ovary in vitro. IGF-1 and IGF-2 had no effect on mRNA levels of several steroidogenesis-related genes (star, cyp11a1, hsd3b, cyp17a2, and cyp19a1). However, both IGFs enhanced the transcription of cyp17a1 in vitellogenic ovaries, although such up-regulation was not found in the ovary at the pre-vitellogenic stage. The stage-dependent effects of IGFs were correlated with changes in ovarian cyp17a1 mRNA levels during the reproductive cycle: transcript abundances increased in conjunction with ovarian development. In addition, IGF-induced cyp17a1 gene expression was significantly inhibited by wortmannin, suggesting that PI3 kinase plays an essential role in IGF-mediated ovarian steroidogenesis. Furthermore, IGF-1 and IGF-2 promoted the conversion of both progesterone and 17α-hydroxyprogesterone to androstenedione in vitellogenic ovaries, suggesting that both IGFs stimulated 17α-hydroxylase and C17-20 lyase activities. Taken together, these findings suggest that IGF-1 and IGF-2 act directly on follicle cells to stimulate steroid production through an increase in gene expression and enzymatic activity of cyp17a1 via induction of PI3 kinase.